PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING DALAM PEMILIHAN MEDIA PROMOSI SEKOLAH (STUDI KASUS DI MTS LABORATORIUM UIN BUKITTINGGI) - Tuti Nabila; Gunadi Widi Nurcahyo; Rini Sovia (Program Studi Sistem Informasi, Universitas Banten Jaya, 2025)
Schools play a strategic role in organizing learning and implementing promotional strategies to increase student enrollment. The use of information technology in promotions is crucial for enhancing institutional competitiveness. MTs Laboratorium UIN Bukittinggi faces challenges in determining the most effective promotional media among various alternatives. While several media have been implemented, the selection process lacks a systematic analytical approach, making it difficult to measure effectiveness objectively. This study applies the Simple Additive Weighting (SAW) method to determine the most effective promotional media. This study represents the first application of the SAW method for selecting school promotional media based on multi-criteria decision-making. The methodology includes defining criteria and weights, inputting alternative data, assessing suitability ratings, normalizing the decision matrix, and ranking alternatives. The dataset was collected from MTs Laboratorium UIN Bukittinggi, evaluating five media alternatives based on four criteria: promotion duration, reach, information completeness, and production cost. The results show that direct socialization achieved the highest final score of 0.91, followed by websites (0.51), banners (0.49), brochures (0.472), and social media (0.33). These findings provide practical guidance for schools in selecting promotional media that are both effective and efficient in attracting prospective students, optimizing resource allocation, and enhancing promotional impact. This study confirms that the SAW method effectively selects promotional media and can assist educational institutions in improving their promotional strategies